2022
DOI: 10.3389/fonc.2021.754149
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Role of Retroperitoneal Lymphadenectomy in 170 Patients With Ovarian Clear Cell Cancer

Abstract: IntroductionWe evaluated the therapeutic role of retroperitoneal lymphadenectomy in patients with ovarian clear cell cancer (OCCC).Materials and MethodsWe retrospectively reviewed 170 OCCC patients diagnosed at two hospitals in China between April 2010 and August 2020. Clinical data were abstracted, and patients were followed until February 2021. Patients were divided into retroperitoneal lymphadenectomy and no lymphadenectomy groups. The Kaplan–Meier method was used to compare progression-free (PFS) and overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…In addition, the prognostic outcomes of patients with distant organ metastases, including liver metastases, lung metastases, brain metastases, and PFS (26.7%), were significantly worse than those without organ metastases (5-year OS: 22.2% vs. 71.8%; 5-year PFS: 26.7% vs. 73.9%) [ 228 ]. In a study based on 170 OCCC patients from China, combined ascites were shown to be an independent risk factor for OCCC patients (HR: 2.354; 95% CI: 1.118–4.762), with a lower 2-year PFS rate in patients compared to those without ascites (87.1% vs. 49.9%) [ 229 ].…”
Section: Prognostic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the prognostic outcomes of patients with distant organ metastases, including liver metastases, lung metastases, brain metastases, and PFS (26.7%), were significantly worse than those without organ metastases (5-year OS: 22.2% vs. 71.8%; 5-year PFS: 26.7% vs. 73.9%) [ 228 ]. In a study based on 170 OCCC patients from China, combined ascites were shown to be an independent risk factor for OCCC patients (HR: 2.354; 95% CI: 1.118–4.762), with a lower 2-year PFS rate in patients compared to those without ascites (87.1% vs. 49.9%) [ 229 ].…”
Section: Prognostic Factorsmentioning
confidence: 99%
“…This was further supported by the findings of Wang and colleagues (HR: 1.097; 95% CI: 1.006–1.195) [ 236 ]. In addition, several studies have shown that age and tumor size are independent risk factors affecting the prognosis of OCCC patients [ 228 , 229 ].…”
Section: Prognostic Factorsmentioning
confidence: 99%